Application of minimum curvature method to well path calculations - Amorin, R.; Broni-Bediako, E. (University of Mines and Technology, 2010)
A major drawback of directional and horizontal well drilling is the numerous complex computations required to be done while planning a well. These computations are very stressful and time consuming especially when done manually. One of the objectives of this study was to develop a user friendly Excel Spreadsheet program that would make the computations of these well trajectory parameters easier, faster and accurate. An Excel Spreadsheet program was developed employing the Minimum Curvature method (and for other five methods) for wellpath design and planning. This would help increase the usage of these trajectory methods especially the Minimum Curvature method. The program is able to provide pictorial views both in the vertical and horizontal plane of the trajectory of the drilling bit’s position in the wellbore. This would therefore help to minimize risk and uncertainty surrounding hitting predetermined target. This is possible because deviations can easily be detected and the necessary directional corrections or adjustment be initiated to re- orient the drilling bit to the right course before (planning process) and during the drilling operations
Keywords: Drilling; Calculations; Curvature method; Extractive industry